The Concept of Buying and Selling in Muamalah Fiqh: Study of Harmony, Transaction Terms and Prohibitions - Salma Rahmawati Ramadani; Shafa Kamila; Rege Rusliyane; Lutfi Saepul Akbar; Muhamad Ibnu Malik (Konsultan Jurnal Ilmiah Indonesia, 2025)
Buying and selling constitute one of the most fundamental contracts in Islamic economic activities. In Islam, commercial transactions are not merely viewed as economic practices but also as legal and social activities that must comply with Islamic law. This article aims to analyze the concept of buying and selling from the perspective of fiqh muamalah through a literature review focusing on the pillars, conditions, and prohibitions of transactions. This study employs a qualitative approach using library research methods, drawing on classical fiqh sources, contemporary Islamic jurisprudence literature, and relevant scholarly articles. The findings indicate that the validity of a sale contract depends on the fulfillment of its pillars and conditions, as well as the absence of prohibited elements such as usury (riba), uncertainty (gharar), and fraud. Furthermore, the principles of fiqh muamalah remain relevant and adaptable in addressing contemporary economic transactions. Therefore, the consistent application of these principles is expected to contribute to the development of a fair, transparent, and Sharia-compliant economic transaction system in accordance with the objectives of Islamic law (maqāṣid al-sharī‘ah). This study emphasizes that a profound understanding of the normative aspects of buying and selling is crucial amidst the rapid digitalization of the economy. By integrating values of honesty and transparency into modern business models, Muslim economic actors can ensure that technological innovations go hand-in-hand with Sharia ethical principles, thereby providing legal protection for all parties involved.